2013
DOI: 10.1128/jvi.01853-12
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interferon Regulatory Factor 3-Mediated Apoptosis in the Establishment and Maintenance of Persistent Infection by Sendai Virus

Abstract: Infection of cultured cells by paramyxoviruses causes cell death, mediated by a newly discovered apoptotic pathway activated by virus infection. The key proapoptotic protein in this pathway is interferon regulatory factor 3 (IRF-3), which upon activation by virus infection binds BAX, translocates it to mitochondria, and triggers apoptosis. When IRF-3-knockdown cells were infected with Sendai virus (SeV), persistent infection (PI) was established. The PI cells produced infectious SeV continuously and constituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Besides its key role in antiviral immunity, IRF3 activation by virus infection is essential for triggering a direct apoptotic response, as manifested by the fact that infected cells are not killed in the absence of IRF3 and become persistently infected (53)(54)(55). In agreement, we have recently demonstrated that IRF3 mediates apoptosis in response to dsRNA in androgensensitive PCa cells (56) as well as, as previously observed, in melanoma and fibrosarcoma cells (57).…”
Section: Tlr3 and Src Mediate Apoptosis Independently Of Irf3supporting
confidence: 88%
“…Besides its key role in antiviral immunity, IRF3 activation by virus infection is essential for triggering a direct apoptotic response, as manifested by the fact that infected cells are not killed in the absence of IRF3 and become persistently infected (53)(54)(55). In agreement, we have recently demonstrated that IRF3 mediates apoptosis in response to dsRNA in androgensensitive PCa cells (56) as well as, as previously observed, in melanoma and fibrosarcoma cells (57).…”
Section: Tlr3 and Src Mediate Apoptosis Independently Of Irf3supporting
confidence: 88%
“…The ability of LCMV to block RIG-I/MAVS-mediated induction of IFN-I but not apoptosis seemed contradictory to recent studies by Chattopadhyay and colleagues that revealed a lower activation threshold of IRF3 for the IFN-I response than for apoptosis (51). To address this apparent contradiction, we evaluated the role of RIG-I and MAVS in virus-induced apoptosis in LCMV-pi cells.…”
Section: Discussionmentioning
confidence: 67%
“…RAW264.7 cells challenged with infectious ATCV-1 exhibited a cytopathic effect and/or died by 72 h. Virus-activated apoptosis is a key antiviral mechanism that limits viral replication (19) but could also contribute to viral persistence through macrophage phagocytosis of apoptotic virus-infected cells (20). Cleavage of caspase 3 (21) and binding of annexin V to phosphatidylserine at the cell membrane (22) are hallmarks of apoptotic cell death.…”
Section: Atcv-1 Was Taken Up By and Persisted Within Macrophagesmentioning
confidence: 99%